Islamic Movements in Indonesia: A Critical Study of Hizbut Tahrir Indonesia and Jaringan Islam Liberal - Ali Maksum,; Irwan Abdullah,; Siti Mas'udah,; Muhammad Saud, (Journal of Al-Tamaddun, 2022)
For all religions, including Islam, pluralism in society is a challenge. Many thought reconstructions and debates regarding the Islamic paradigm are results of conflicts between right and left Islamic ideologies about the religious paradigm. This research aimed to determine how Jaringan Islam Liberal (JIL) and Hizbut Tahrir Indonesia (HTI) groups embrace tolerance and social networks. The data were analyzed using van Dijk’s critical discourse analysis and a multi-level approach to offer a more critical understanding of the paradigms. This research discovered that JIL has promoted religious tolerance within its theological domain, while HTI has reacted adversely. HTI has not renounced tolerance, but its ideology does not include religious tolerance. HTI derives its legitimacy from Islam; its activists see Islam as a religion and an ideology. JIL also views religion as more than just text and pursues a contextual view of theology. Meanwhile, HTI was restricted to its textual interpretation. Its dissemination in several media outlets further demonstrated its paradigm and the unity of HTI members.